Nanoparticles as macromolecules. Issue 16 (27th June 2013) - Miller, Joseph B.; Hobbie, Erik K.
Abstract A review of recent trends in the dispersion, purification, and assembly of colloidal nanoparticles highlights a number of growing analogies with ideas borrowed from polymer science. Beyond the similar scales of size, several key concepts lying at the foundation of polymer physics—such as polydispersity, fractionation, phase ordering, and viscoelasticity—are taking on new and unique significance in the contemporary realm of nanotechnology. Leveraging "soft matter" at the nanoscale to simplify materials processing and improve material performance is becoming a reality, with potentially profound implications for a number of emerging technologies. © 2013 Wiley Periodicals, Inc. J Polym Sci Part B: Polym. Phys. 2013, 51, 1195–1208